已知数列{an},{bn}满足:a1=3b1=3,a2=6,bn+1=2bn-2n,bn=an-nan-1(n≥2,n∈N*). (I)探究数列{
(II)求数列{nan}的前n项和Sn. |
(I)∵bn+1=2bn-2n ,∴bn+1-2bn =-2n ,∴
- bn+1 2n+1
=-bn 2n
.1 2
∴数列{
}构成以bn 2n
为首项,以-1 2
为公差的等差数列,∴1 2
=bn 2n
-1 2
(n-1),1 2
∴bn=2n(1-
).n 2
(II)∵bn=an-nan-1,∴an-2n=nan-1-n2n-1=n( an-1-2n-1 ),
∴
=n,an- 2n an-1-2n-1
∴
=an- 2n a1-2
•an- 2n an-1-2n-1
•an-1-2n-1 an-2-2n-2
…an-2-2n-2 an-3-2n-3 a2-22 a1-2
=n(n-1)(n-2)×…×3×2,又 a1=3,故 an=n(n-1)(n-2)×…×3×2×1+2n,
nan=n×n(n-1)(n-2)×…×3×2×1+n 2n=(n+1)!-n!+n 2n,
∴sn=(2!-1!)+(3!-2!)+(4!-3!)+…+((n+1)!-n!)+(1×2+2×22+…+n2n )
=(n+1)!-1+( 1×2+2×22+…+n2n ).
令Tn=1×2+2×22+…+n2n,①则 2Tn=1×22+2×23+…+n 2n+1,②
①-②可得,-Tn=2+22+23+…-n 2n+1,∴Tn=(n-1)2n+1+2,
∴sn=(n+1)!+(n-1)2n+1+1.